Crime in cyberspace: the digital underworld. - Stephens, Gene (Futurist)
As computers become more prevalent and easier to use, criminals are learning to use them for profit and malice. Increasingly, the benign “hacker” is being replaced by the threatening “cracker,” an individual or member of a group intent on using cyberspace for illicit profit or terrorism. Invulnerable protection systems can probably never be developed, although some high-tech entrepreneurs are trying. Even if a completely secure system was developed, it would be likely to obstruct the free flow of information—an unacceptable intrusion for most cyberspace users. The use of computers to commit communications crimes, cybercrimes against the government, business crimes, cyberstalking, remote terrorism, and virtual crimes is discussed.